(untitled) (Perner’s Contacts, 2009)
Forecasting and prognosis have a signification in the course of actual various conditions. Knowledge of development of passenger transport makes it possible to economize of public funds. The paper describes term forecasting and prognosis, analyses information which is necessary to make prognosis of development of passenger transport. Further the paper is concerned to prognosis of development of passenger transport by using of adequate quantitative and qualitative methods.